Detection of Zika Virus in Aedes aegypti and Aedes albopictus Mosquitoes Collected in Urban Forest Fragments in the Brazilian Amazon - Erika Oliveira Gomes; Lívia Sacchetto; Maurício Teixeira; Bárbara Aparecida Chaves; Adam Hendy; Claudia Mendonça; Izabele Guimarães; Ramon Linhares; Daniela Brito; Danielle Valério; Jady Shayenne Mota Cordeiro; Alexandre Vilhena Silva Neto; et al. (Viruses, 2023)
Zika virus (ZIKV) is an RNA flavivirus (Flaviviridae family) endemic in tropical and subtropical regions that is transmitted to humans by Aedes (Stegomyia) species mosquitoes. The two main urban vectors of ZIKV are Aedes aegypti and Aedes albopictus, which can be found throughout Brazil. This study investigated ZIKV infection in mosquito species sampled from urban forest fragments in Manaus (Brazilian Amazon). A total of 905 non-engorged female Ae. aegypti (22 specimens) and Ae. albopictus (883 specimens) were collected using BG-Sentinel traps, entomological hand nets, and Prokopack aspirators during the rainy and dry seasons between 2018 and 2021. All pools were macerated and used to inoculate C6/36 culture cells. Overall, 3/20 (15%) Ae. aegypti and 5/241 (2%) Ae. albopictus pools screened using RT-qPCR were positive for ZIKV. No supernatants from Ae. aegypti were positive for ZIKV (0%), and 15 out of 241 (6.2%) Ae. albopictus pools were positive. In this study, we provide the first-ever evidence of Ae. albopictus naturally infected with ZIKV in the Amazon region.